Analysis Of The Influence Of Debt Policy, Company Size And Corporate Governance On Agency Costs For Property Companies In Indonesia - Mirza Anindya Pangestika; Aprilya Dwi Yandari; Hildawati; Ngurah Pandji Mertha Agung Durya; Ratnawita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to investigate how agency cost is impacted by corporate governance mechanisms, company size, and debt policy. The study's independent variables include audit committees, institutional ownership, and the number of commissioners in corporate governance structures. Next, determine the company's size using the natural log of its assets and its debt policy, which is determined by dividing its total assets by its liabilities. Using the sales to total assets ratio, agency cost is the dependent variable in this study. In this study, secondary data are used. The property businesses that were listed on the IDX between 2019 and 2021 made up the study's population. Purposive sampling was used to choose the research sample, yielding 50 firms annually. Following data processing according to the chosen criteria, some firms made up the sample, which meant that some companies was the final sample size that was employed. Multiple regression analysis models are used in the analysis test. The study's findings show that debt policy and the board of commissioners have a big impact on agency costs. However, the size of the business, the audit committee, and institutional ownership have little impact on agency costs.